Multiple positive solutions to a fourth-order boundary-value problem - Alberto Cabada; Radu Precup; Lorena Saavedra; Stepan A. Tersian (Electronic Journal of Differential Equations, 2016)
We study the existence, localization and multiplicity of positive solutions for a nonlinear fourth-order two-point boundary value problem. The approach is based on critical point theorems in conical shells, Krasnoselskii's compression-expansion theorem, and unilateral Harnack type inequalities.